Negotiating Space, Emotion, and Belonging: A Critical Socio-Spatial Approach to Iranian Immigrant Integration in Toronto - Valizadeh, Negar (Université d'Ottawa / University of Ottawa, 2025)
This doctoral thesis aims to reconceptualize immigrant settlement narratives through a critical socio-spatial lens, focusing on the case of established, predominantly economic-class Iranian immigrants in Toronto, Canada. By interrogating residential choices, integration pathways, community-building practices, and homemaking strategies, the study challenges traditional models of immigrant settlement, foregrounding the agency of skilled Iranian immigrants in shaping spaces of belonging within a multicultural metropolis. The analysis integrates Lefebvre's (1991) theory of the social production of space, Askins' (2016) concept of emotional citizenry, and social capital theory (Putnam, 1993; Woolcock, 1998) to analyze how Iranian immigrants negotiate place and identity. The thesis comprises four interconnected articles. The first interrogates residential concentration in Toronto's affluent northern suburbs through Lefebvre's spatial triad, challenging existing models of immigrant settlement and suburbanization. Using Askins' emotional citizenry, the second article examines the complex interplay between residential and socioeconomic integration, highlighting gendered experiences and emotional belonging. The third investigates multiscale community-building practices, showing how bonding, bridging, and linking social capital, in combination with emotional citizenry, foster affective attachments across private and public spheres. The fourth article frames homemaking as a spatial practice that, through Lefebvre's triad, actively reconfigures suburban homes and environments into contested sites of cultural preservation and identity negotiation. Employing a mixed-methods approach - including census data analysis, 54 semi-structured interviews with photovoice, ethnographic observations, and 7 key informant interviews - the methodology aligns with the conceptual framework's emphasis on spatial production and affective agency. The study makes three key contributions. First, it offers an integrated conceptual framework bridging structural spatial analysis (Lefebvre) and emotional agency (Askins), challenging deficit-oriented settlement models. Second, it repositions integration as an active, multidimensional process through which immigrants leverage (suburban) spaces to reconcile cultural heritage with social mobility aspirations. Finally, it provides a multiscalar account of how immigrants mobilize social capital across spatial and institutional contexts to foster emotional belonging.
Keywords: Iranian immigrants; residential patterns; integration processes; community-building practices; homemaking strategies; skilled economic immigrants; emotional belonging